2010
DOI: 10.1007/s11999-010-1432-3
|View full text |Cite
|
Sign up to set email alerts
|

Total Ankle Replacement Compatible with Ligament Function Produces Mobility, Good Clinical Scores, and Low Complication Rates: An Early Clinical Assessment

Abstract: Background A three-part ankle replacement was developed to achieve compatibility with the natural ligaments by allowing fibers on the medial and lateral sides to remain isometric during passive motion. Unlike all current prostheses, the new design uses nonanatomically shaped components on the tibia and talus and a fully conforming interposed meniscal bearing.Questions/purposes Does this new design restore ankle mobility, improve clinical score, and result in low complication and early revision rates? Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 41 publications
2
28
1
Order By: Relevance
“…14 The New Zealand registry reports a five-year survival rate of 86% and the Finnish registry a seven-year survival rate of 78%. 15,16 Despite the fact that our survival rate was similar to those reported in the literature, it was still low compared with that reported by Giannini et al 2 In our study, there was a discrepancy between the range of movement measured clinically and radiologically. The range of movement measured clinically is the combined range of movement of the joints of the midfoot and hindfoot.…”
Section: Fig 2asupporting
confidence: 52%
See 2 more Smart Citations
“…14 The New Zealand registry reports a five-year survival rate of 86% and the Finnish registry a seven-year survival rate of 78%. 15,16 Despite the fact that our survival rate was similar to those reported in the literature, it was still low compared with that reported by Giannini et al 2 In our study, there was a discrepancy between the range of movement measured clinically and radiologically. The range of movement measured clinically is the combined range of movement of the joints of the midfoot and hindfoot.…”
Section: Fig 2asupporting
confidence: 52%
“…It aims to maintain normal collateral ligament function, thereby keeping the articular surfaces in contact throughout the entire range of movement. 2,3 Giannini et al 2 recently reported the results of a prospective multicentre study of the first 51 BOX TARs, implanted between 2003 and 2006, with a mean follow-up of 30 months. This showed a three-year cumulative survival rate of 97% and a mean American Orthopedic Foot and Ankle Society (AOFAS) score 4 of 76.9 points.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed that kinematics of the natural ankle were mimicked using other anatomical (Valderrabano et al, 2003) and non-anatomical (Reggiani et al, 2006) three-component designs during in vitro experiments. However, during in vivo conditions, other factors such as periarticular ligaments and implant position may be different from in vitro simulation, and they contribute to its kinematics (Giannini et al, 2010). Further research is necessary to elucidate in vivo function of each TAA design.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike all current prostheses, the new design uses non-anatomically shaped components on the tibia and talus, and a fully conforming interposed meniscal bearing. The new prosthesis can provide short-term restoration of ankle mobility, a good clinical score, and low complication and failure rates (134).…”
Section: Total Ankle Replacementmentioning
confidence: 97%